The institutionalization of pharmaceutical care in the municipality of Ananindeua, Pará (Research, Society and Development, 2021)
Objective: Contextualize the adaptation to current regulatory frameworks, the links with the instruments of governance, management and planning, structure and organization and actions, activities, and tasks inherent to the technical-assistance and technical-managerial field of pharmaceutical assistance in the municipality of Ananindeua, Pará Method: This is an action-research, exploratory, descriptive, and analytical carried out in 2019 and 2020. Result: 17 District Pharmacies and 03 Specialized Pharmacies in Basic Health Units, strategic for accessibility and access, were structured and organized. with 51 pharmacists and with the management of stock control done via the National System of Pharmaceutical Assistance Management (Horus System). As for the institutionalization of Pharmaceutical Care, there were gaps in compliance with governance practices, management, planning, monitoring and evaluation of pharmaceutical care, such as indicators related to technical management of pharmaceutical care, clinical drug management and sectorial policies. Conclusion: The municipality of Ananindeua, Pará, needs to consolidate the process of institutionalization of pharmaceutical care. There are still gaps, both related to technical-managerial and technical-assistance components.